Reverting to traditional views of gender during times of relative deprivation: An experimental study in Nepal - Kosec, Katrina; Mo, Cecilia Hyunjung; You, Soosun; Boittin, Margaret (International Food Policy Research Institute, 2023)
Do individuals’ perceptions of their relative economic status affect their attitudes regarding gender roles in patriarchal societies? What role does hearing messages designed to increase support for women’s empowerment play in moderating these effects? Leveraging an original survey experiment in Nepal, we find that a prime conferring feelings of relative deprivation causes women to revert to traditional views of gender in economic decision-making; they become less supportive of women having equal control over household income, sharing house hold chores with men, and working outside the home. Women’s empowerment messaging does not attenuate these effects. Priming men to feel relatively deprived causes declines in gender equitable economic and political views, but women’s empowerment messaging nullifies these effects. The results suggest that among populations feeling relatively deprived, regressive gender norms may take hold. However, light-touch efforts to spur support for women’s empowerment may counter some reversion to traditional views of gender.